Correlation between METTL3 overexpression and 18F-FDG uptake in patients with soft tissue sarcoma - Tong Wu; Jinghui Xie; Hongbo Feng; Hua Zhang; Juan Tao; Bo Chen (BMC Cancer)
Abstract Background N6-methyladenosine (m6A) methylation plays a key role in tumor progression. However, the significance of methyltransferase-like 3 (METTL3) in biological processes of soft tissue sarcoma (STS) patients, and the relationship between METTL3 and STS are unclear. Methods The expression of METTL3 in STS and its relationship with patient prognosis were determined from database analyses. Immunohistochemical staining and 18F-FDG radioautography were performed on tumor tissues from 39 patients with STS undergoing 18F-FDG PET before treatment. METTL3 expression in tumor and peritumoral tissues was evaluated with the Wilcoxon test. The Mann-Whitney U test and Spearman’s correlation analysis were used to explore correlations of METTL3 expression with both clinicopathological characteristics and 18F-FDG uptake. One-way analysis of variance and ROC analysis were used to evaluate the efficacy of 18F-FDG PET metabolic parameters in predicting METTL3 expression. Results METTL3 expression was significantly higher in STS tumor tissues than normal tissues (all p values<0.01), and correlated with poor patient prognosis (p < 0.05). METTL3 expression was associated with histological differentiation (Z=-2.026, p = 0.043), but no significant difference was observed according to age, sex, tumor size, tumor location, or metastasis (all p values > 0.05). METTL3 expression positively correlated with the expression of CD163 (r = 0.502, p = 0.011), CD68 (r = 0.381, p = 0.017), and CD8 (r = 0.319, p = 0.048), and exhibited a trend toward correlation with CD4 expression (r = 0.310, p = 0.055). Moreover, 18F-FDG metabolism positively correlated with METTL3 expression in STS (r = 0.580 for PET and r = 0.434 for radioautography, all p values<0.01). The SUVmax of PET was significantly higher in tumors with high rather than low METTL3 expression (Z=-2.979, p = 0.003). Conclusions METTL3 was overexpressed in STS, which may be a meaningful target of action in STS patients. The 18F-FDG uptake was significantly elevated in tumors with high METTL3 expression, SUVmax could provide a meaningful imaging biomarker for its expression.